FACTS ANALYSIS OF THE STORY IN THE NOVEL DUNIA KELABU BY DIONE PYRENA AND DAVY SHAN - I. Irwan; Imelda Lestari Hasan (Journal of Indonesian Language Education and Literary, 2017)
This research was motivated by the facts of the story that is one aspect of the surface structure of literary works. It is important to study deeper understanding of structures in literary works. The facts of the story discuss three aspects, namely (1) plot, (2) figures, and (3) setting. The objective of this research was to describe facts of the story in the novel Dunia Kelabu by Dione Pyrena and Davy Shan. This research includes the type of literature research. The method used was descriptive method. The data in this study was written data in the form of words, phrases, clauses, sentences, and paragraphs that contained facts of the story. Source of data in this research was the novel Dunia Kelabu by Dione Pyrena and Davy Shan. Techniques of data collection used reading and writing techniques. Data analysis technique used ws structural theory. The results showed that the plot was used namely the forward plot. The character consisted of 14 characters, namely (1) Dione, (2) Davy, (3) Mother, (4) Father, (5) Mother's parents, (6) Father's parents, (7) Father's brother, (8) Mother's brother, (9) Street friends, (10) Doctor, (11) Mbak/sister Heni, (12) Komnas staff, (13) Kak/brother Seto, and (14) Kak Seto's wife (Devy). The characters were described on the basis of Dione and Davy as the main characters, Father and Mother as additional figures, Dione, Davy, and Mother as protagonists, Father as antagonist, Dione as a round figure, Davy as a modest figure, Father as a static figure, Dione as a developing figure, Mother as a typical figure, Dione and Davy as neutral figures. The background used was the background of the place and time setting. Background of place used namely (1) House, in Bandung, (2) School, and (3) Sidewalks. Background of time used namely (1) Afternoon, (2) Night, and (3) Month.